Ion-molecule reactions of CoAr6+ with nitrogen oxides N2O, NO, and NO2: measuring absolute pressure by shock-freezing of the collision complex - Linde, C. van der; Höckendorf, R.F.; Balaj, O.P.; Beyer, M.K. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
A new method to determine the absolute pressure in an ultra-high vacuum apparatus is tested using ion molecule reactions with CoAr6+. In a collision with a neutral reactant, the complex between Co+ and the collision partner is stabilized by evaporation of argon atoms. If CoAr6+ reacts with collision rate, the absolute pressure can be determined by comparing the experimental collision rate with the collision rate calculated from averagedipole orientation theory. The experimental results with N2O, NO and NO2 indeed show that the collision complexis frozen out. Comparison of the rates of primary, secondary and tertiary reaction products, however, suggests that not all collisions of CoAr6+ are reactive.